2008
DOI: 10.1016/j.neuroscience.2008.09.050
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to an open-field arena increases c-Fos expression in a subpopulation of neurons in the dorsal raphe nucleus, including neurons projecting to the basolateral amygdaloid complex

Abstract: Serotonergic systems in the dorsal raphe nucleus are thought to play an important role in the regulation of anxiety states. To investigate responses of neurons in the dorsal raphe nucleus to a mild anxiety-related stimulus, we exposed rats to an open-field, under low-light or high-light conditions. Treatment effects on c-Fos expression in serotonergic and non-serotonergic cells in the midbrain raphe nuclei were determined 2h following open-field exposure or home cage control (CO) conditions. Rats tested under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 47 publications
4
59
0
3
Order By: Relevance
“…(2,27) ϭ 7.45; *p Ͻ 0.05; n ϭ 12; E) without changing the total moving distance (vehicle, 3746.22 Ϯ 1168.60 cm; diazepam, 0.5 mg/kg, 3778.29 Ϯ 1316.09 cm; n ϭ 12; F (2,27) ϭ 0.56, not significant; F ). Hale et al (2008) reported that the exposure of rats to an OF arena markedly increases c-Fos expression in both TPHpositive and TPH-negative neurons in the DRL. In the present study, we confirmed this and further revealed that diazepam suppressed the OF stress-induced c-Fos expression at a dose that effectively lowered the anxiety level.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…(2,27) ϭ 7.45; *p Ͻ 0.05; n ϭ 12; E) without changing the total moving distance (vehicle, 3746.22 Ϯ 1168.60 cm; diazepam, 0.5 mg/kg, 3778.29 Ϯ 1316.09 cm; n ϭ 12; F (2,27) ϭ 0.56, not significant; F ). Hale et al (2008) reported that the exposure of rats to an OF arena markedly increases c-Fos expression in both TPHpositive and TPH-negative neurons in the DRL. In the present study, we confirmed this and further revealed that diazepam suppressed the OF stress-induced c-Fos expression at a dose that effectively lowered the anxiety level.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, c-Fos expression induced by OF stress in the DRD and DRV was resistant to diazepam. Because these nuclei project not only to the basolateral amygdala (Hale et al, 2008), but also to the medial prefrontal cortex and nucleus accumbens (Van Bockstaele et al, 1993), the c-Fos induction in these nuclei may be related to the cognition or novelty-seeking behaviors. Together, these findings suggest that neurons in the DRL, particularly 5-HT/GAD67 neurons, are highly sensitive to innocuous stressors, in which activation of diazepam-sensitive GABA A receptors may be involved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data demonstrate a relationship between the integrative actions of all urocortins in modulating stress responses. Increases in the above-noted anxiety indices were reported following different paradigms of stress exposure and were related to altered structure and/or functions of stress-related neurocircuits, including the amygdalar-BNST complex, septal regions, raphe nuclei serotonergic circuits, and HPA-axis regulation (29)(30)(31)(32)(33)(34)(35).…”
Section: (G and H) Asr (G)mentioning
confidence: 99%